PPO.21 Altered maternal hypothalamic-pituitary-adrenal axis activity in obese pregnancy: a potential mechanism underlying macrosomia and prolonged pregnancy. (9th June 2014) - Stirrat, LI; O'Reilly, JR; Riley, SC; Howie, AF; Smith, R; Walker, BR; Norman, JE; Reynolds, RM
Abstract : Background: Increased hypothalamic-pituitary-adrenal (HPA) axis activity has been associated with low birthweight and preterm labour. Maternal obesity is associated with macrosomia (birthweight ≥4000 g) and prolonged pregnancy (≥41 weeks). We hypothesised altered HPA axis activity may underlie these pregnancy outcomes and aimed to characterise HPA axis hormones in obese pregnancy. Method: Fasting serum cortisol was measured by radioimmunoassay at 16, 28 and 36 weeks in 286 obese (BMI 44.05 ± 3.98 kg/m 2 ) and 137 lean (BMI 22.71 ± 1.66 kg/m 2 ) pregnant women. In subsets (n = 20 obese, 20 lean) we measured corticosteroid-binding-globulin (CBG) and corticotrophin-releasing-hormone (CRH) by radioimmunoassay. Free cortisol was calculated using Coolen's equation. Results: Cortisol was significantly lower throughout pregnancy in obese (Table 1), and lower free cortisol at 16 weeks was associated with higher birthweight (r = -0.46, p < 0.05). Lower CRH at 28 weeks correlated with later gestation at delivery in obese (r = -0.56, p < 0.05) and remained significant as an independent predictor of gestation at delivery (beta = -3.19; p < 0.05). Lower CRH at 36 was associated with delivery ≥41 weeks (236.4 ± 172.7 pmol/L vs. 271.9 ± 233.8 pmol/L; p < 0.05) and with macrosomia (108.68 ± 31.7 pmol/L vs. 291.09 ± 216.32 pmol/L; p < 0.05). Conclusion: Decreased HPA axis activity in obese pregnancy may underlie macrosomia and prolonged pregnancy.